Karakteristik Fruit Leather Kering dari Apel (Malus sylvestris) dan Buah Naga Merah (Hylocereus polyrhizus) - Marina Revitriani; Tri Rahayuningsih; Fungki Sri Rejeki; Endang Noerhartati (Faculty of Agricultural Technology, University of Jember, 2022)
Processing apples into products such as fruit leather is an effort to extend its shelf life, provide added value, easy to distribute, and potentially an export product, but it has an unattractive color, so it needed to combine with red dragon fruit. In addition, fruit leather has water content of 10-20%, so it has a limited shelf life. Therefore, it’s necessary to study dried fruit leather. This study aimed to determine the characteristics of dried fruit leather made from apple and dragon fruit. The experimental design used a randomized block design (RBD) with two factors, i.e. proportion of apples and red dragon fruits (75%:25%, 50%:50%, 25%:75%) and citric acid concentration (0%, 0.1%). The combination of those treatments was conducted in triplicate. Elasticity, tensile strength, L*a*b color, water content, total sugar, and vitamin C were parameters observed of the dried fruit leather. Sensory testing used a rank test of taste, color, texture, and aroma preferences. The data were analyzed by ANOVA (α=5%). If there was a difference, Duncan's test was performed. The Friedman test was used to analyze organoleptic test data. The results showed that there was an interaction between treatments on each parameter and between the treatments of the panelists' preference for the color and texture of the dried fruit leather. The characteristics of dried fruit leather have ranges of elasticity 13.00–33.00%, tensile strength 1.2–3 N, water content ranges from 1.3–5.3%, total sugar ranges from 67.30–71.70%, and vitamin C ranges from 50.00 mg/100g–94.00mg/100g. Brightness values ​​(L) range from 29.50 to 31.40, a* values ​​range from 12.9 to 17.7(red), and b* values ​​range from -8.2 to -14.8 (blue). Apple and red dragon fruit can make into dried fruit leather, which has a reddish-blue color. Keywords: apple, citric acid, dragon fruits, dried fruit leather